Scheduling Smart Grid Network Traffic with Context-Awareness in Industrial Grade Router - Wan Ahmad W.S.H.M.; Radzi N.A.M.; Ridwan M.A.; Mustafa I.S.; Suhaimy N.; Samidi F.S.; Nasir M.H.M.; Abdullah F.; Ismail A.; Jamaludin M.Z.; Zakaria M.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Packet switching; Scheduling; Smart power grids; Context- awareness; Context-Aware; Controlled environment; Data rates; Priority assignment; Smart grid networks; Test case; Traffic scheduling; Electric power transmission networks